1991
DOI: 10.2307/2409924
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Stiffness Allometries of Angiosperm and Fern Petioles and Rachises: Evidence for Biomechanical Convergence

Abstract: Evidence for convergence in biomechanical and anatomical features of leaves (elastic modulus E, second moment of area I, taper of petioles, the longitudinal distribution of petiolar and laminar weight, and volumes of tissues) is presented based on a survey of 22 species (distributed among dicots, monocots, and ferns). In general, regardless of taxonomic affinity, petioles were found to be mechanically constructed in one of two ways: Type I petioles-as cantilevered, end-loaded beams with relatively uniform flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 11 publications
1
40
0
1
Order By: Relevance
“…Previous work in two species has shown that petiole cross-sectional area correlates with supported mass and area within species (Niklas 1991a; Yamada et al 1999). Additionally, several studies have examined relationships among petiole biomechanical properties within and across species (Niklas 1991a(Niklas ,b, 1994(Niklas , 1999. Our study is the first to our knowledge to demonstrate general scaling between petiole and lamina dimensions across diverse species, and to develop from these interrelationships a prediction of M^.…”
Section: Model Fitting and Justificationmentioning
confidence: 51%
See 4 more Smart Citations
“…Previous work in two species has shown that petiole cross-sectional area correlates with supported mass and area within species (Niklas 1991a; Yamada et al 1999). Additionally, several studies have examined relationships among petiole biomechanical properties within and across species (Niklas 1991a(Niklas ,b, 1994(Niklas , 1999. Our study is the first to our knowledge to demonstrate general scaling between petiole and lamina dimensions across diverse species, and to develop from these interrelationships a prediction of M^.…”
Section: Model Fitting and Justificationmentioning
confidence: 51%
“…However, previous experiments that mimicked the fossilization process indicated little to no change in the two-dimensional shape of leaf blades and at most a 10% inflation in the width of xylem-rich tissues, such as petioles, that are buried in fine-grained sediment (Wal-ton 1936;Niklas 1978;Rex and Chaloner 1983;Rex 1986) such as the two fossil locahties studied here (MacGinitie 1969;Wolfe and Wehr 1987); a 10% inflation of PW would lead to a 7.6% overestimation of M^.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations